Implementasi Teknologi Produksi dan Digitalisasi Pemasaran Dalam Upaya Meningkatkan Daya Saing Produk Krupuk Rambak Sapi Pada Studi Kasus UMKM UD. IKABA di Pasar Global - Sholihah Ayu Wulandari; Qonitatul Hasanah; Adi Sucipto; Ahmad Fahriyannur Rosyady; Asmunir Asmunir (Journal of Community Development, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in boosting Indonesia’s GDP, contributing 61.97%. In addition to generating employment, MSMEs promote economic equity and support national growth. Mojokerto Regency, with 474,346 MSME units contributing IDR 63.498 trillion to the GDP, demonstrates significant potential. However, many MSMEs in this region struggle with low competitiveness. This community engagement program focuses on empowering MSMEs in the food processing sector, particularly the production of kerupuk rambak (fried cowhide crackers) at UD. IKABA. Key challenges identified include limited technology, such as using a modified washing machine to remove excess oil, as well as conventional marketing methods and unappealing packaging. The intervention involved introducing an automatic oil spinner and providing digital marketing training, including the development of a website application for online orders and promotion. The results show improved production efficiency, with processing time reduced by 25%, production capacity increased by 50%, and higher product quality in terms of hygiene and shelf life. Digital marketing also expanded the market reach from local to national levels, resulting in a 70% increase in sales. The implementation of production technology and digital marketing has proven effective in enhancing MSME competitiveness, contributing to both local and national economic growth.